Fostering innovation in large companies through collaboration with technology startups: Examples in Serbia - Sandra Nešić (Anali Ekonomskog fakulteta u Subotici, 2020)
In the global, dynamic and competitive environment innovation has become the main criterion by which it is possible to assess how well a company is doing business and how well it will perform in the future. In the context of the openness of innovation processes, establishing partnerships with the aim of collaboration in the field of innovation enhancement becomes the source for growth and competitiveness of companies. The paper emphasizes the importance of large companies and technology startups' collaboration. Research and the conducted analysis of the business practices of participants in these processes in Serbia indicate multiple significant benefits for collaborators. As young innovative and fast-growing organizations, startups are enabled with more opportunities for faster expansion of business in existing and new markets, using available resources of large companies, gaining necessary credibility to existing and potential customers as well as competitors. On the other hand, large companies are gaining access to innovative ways to improve their innovation capabilities, revenue growth and competitiveness.